Sistem Pendukung Keputusan Team Survei Terbaik Pada SNI (Serikat Nelayan Indonesia) Menggunakan Metode SMART (Studi Kasus: Sekretariat SNI, Medan) - Muhammad Yusuf; Nelly Astuti Hasibuan (Jurnal Sistem Komputer dan Informatika (JSON), 2021)
Surveys are usually confused with the term observation in the everyday sense, surveys are also the main way to collect primary data if secondary data are deemed incomplete to answer a question, if the secondary data is complete enough and the hypothesis can be tested with secondary data then Direct primary data collection using the survey method is no longer necessary, a survey is looking for detailed factual information that is currently symptomatic and identifying problems or to justify conditions and ongoing activities to find out what people are doing which is the target of research in solving problems, as material for planning and making decisions in the future. SMART (Simple Multi - Attribute Rating Technique) is a multi-criteria decision-making method developed by Edward in 1977.This multi-criteria decision-making technique is based on the theory that each alternative consists of a number of criteria that have values and each criterion has a weight describes how important it is compared to other criteria. This weighting is used to assess each alternative in order to obtain the best alternative. SMART uses a linear additive model to predict the value of each alternative. SMART is a flexible decision making method.